ILMU KOLONIAL DI MALAYSIA: PERSPEKTIF MAQASID SYARIAH - Ahmad Farid Abdul Jalal; Rahimin Affandi Abd. Rahim; Ab. Halim Ismail; Huzaimah Ismail; Muhammad Ikhlas Rosele (Pascasarjana UIN ANTASARI Banjarmasin, 2017)
As a country that once colonized by the British, Malaya indeed vulnerable to the influence of British ideology. This occurs through a mechanism of colonial knowledge developed by British to learn and dominate the Malay community. As a result of colonial influence can be traced in all aspects of Malay community life. The findings of this research show that the colonial has their own policies and approach when it comes to the issue of Islam in the Malay community. They try to kill the potential of Islam and replace it with the world-view and British paradigm then embed it into the community. The results of the Maqasid analysis on the legacy of colonial knowledge still prove too much effort to consolidate Islam should be done by Islamic scholars. Islamic scholars have to reject and correct negative outlook placed on Islam.